KEBIJAKAN HUKUM PIDANA TERHADAP TINDAK PIDANA PERBANKAN DI INDONESIA - Fikry Latukau (Musamus University, 2020)
One of the criminal law enforcement efforts, through this instrument, is expected to be able to ward off national banking crimes aimed at disrupting the economic life and national economic system. Characteristics or typologies of banking crime with a new dimension. The new dimension can be seen and discovered at the United Nations Congress, in 1985, the Criminal Law Policy must also see the crime in the banking world as a new crime and must be prevented from developing. In this article, the research method used is normative legal research that emphasizes the use of secondary data material or research material with support from library data. The goal is that the reader can know that in the world developed increasingly sophisticated evil with new dimensions also appear. Therefore, the benefits of this paper are for law enforcers to be able to formulate relevant criminal law policies.